Randomized, Placebo-Controlled, Double-Blind and Open-Label Studies in the Treatment and Prevention of Acute Diarrhea With Enterococcus faecium SF68 - Greuter, Thomas; Michel, Martin C.; Thomann, Daniela; Weigmann, Harald; Vavricka, Stephan R. (Frontiers in Medicine, 2020)
Enterococcus faecium SF68® (SF68) is a licensed pharmaceutical for treatment, prevention of diarrhea in Austria, Italy and Switzerland. However, as for other probiotics, evidence for its efficacy is based on small to medium-sized studies. Four unpublished studies on the on the treatment of acute diarrhea and the prevention of antibiotic-associated diarrhea were analyzed: one randomized, double blind, placebo-controlled trial (RCT) for treatment (n=1143), one open-label study for treatment (n=5093), one RCT for prevention (n=1397) and one open-label study for prevention (n=4340). Patients in the treatment-arm and the open-label studies received SF68 (b.i.d. for the prevention studies, t.i.d. for the treatment trials) for seven days. Primary end points were time to resolution of diarrhea (treatment) and percentage of development of diarrhea (prevention). The primary endpoint of the treatment study was met with a decreased time to resolution of diarrhea in SF68-treated patients compared to controls (median 3 vs. 4 days, p<0.001). Time to resolution of secondary symptoms was also significantly reduced. Preventive treatment with SF68 was more effective than placebo with development of diarrhea in 8.6% vs. 16.2% (p<0.001). Results from the open-label studies were consistent with the RCTs. The incidence of adverse events were low (1.1% and 1.4% in the RCT and 4.7% and 7.4% in the open-label studies). SF68 is effective and safe in the treatment of acute diarrhea and prevention of antibiotic-associated diarrhea.